Quality tools for managing construction projects - Rumane, Abdul Razzak (Industrial innovation series, 2013)
"Quality tools and techniques are very important in developing a comprehensive project quality management system. Application of tools and techniques in construction projects have a great influence on cost effectiveness, results of construction projects, and achieving successful project performance. This book has been developed to provide significant information about usage and applications of various quality tools and techniques for managing a construction project as it moves through the different phases of the project life cycle"-- Provided by publisher.